At arm's length: A qualitative study of suicide prevention barriers among those experienced with suicide loss - Scott J. Fitzpatrick; Kerrie Gallagher; Michelle Banfield; Amelia Gulliver; Alison L. Calear; Stella Conroy; Philip J. Batterham (Elsevier, 2023)
Background: Little attention has been paid to the experiences of families and carers supporting and accessing support for individuals in the period preceding and following their death by suicide. For many families and carers who have experienced loss and been subjected to a series of unhelpful or harmful encounters with health and emergency services, there is a desire to share their stories so that their experiences might contribute to the improvement of practices and policies. Methods: We conducted qualitative interviews with 17 participants supporting and accessing support for individuals who died by suicide in the Australian Capital Territory, Australia. Interviews and thematic analysis were guided by the theoretical frameworks of trauma-informed and restorative practice. Results: Key barriers for those seeking to access support were the difficulties experienced upon entering the health system, inadequate care pathways for ensuring continuity of care, and the lack of trauma-informed, holistic care. Participants described how concerns over their loved one's welfare were minimized by health professionals, and how ineffective communication strategies and the hierarchies of power and control evident in many health care settings were experienced as exclusionary and disempowering. These results provide compelling evidence that emergency services and health workforces require new strategies for effective management and care of people experiencing suicidal distress, their families, and carers. Conclusions: Results support the view that trauma-informed and restorative approaches provide promising strategies for addressing issues of disconnected, fragmented, and exclusionary health care and medico-legal investigative practices, as well as to help resolve conflict and prevent harm.